Effect of plasma treatment on some surface properties of acrylic resin polymer - Masood , Shaymaa H; Mahamed , Salah A (Journal of Baghdad College of Dentistry, 2020)
Background: Polymer surfaces usually present problems in bonding and finishing due to their low hydrophilicity. The aim of this study is to investigate the effect of plasma treatment with the use of two types of gases (oxygen and argon) on surface roughness, and chemical surface properties of acrylic resin denture base polymer material. Materials and Methods: Three heat cured acrylic resin specimens of (2*8*30 mm) dimensions were prepared for each test carried out in this study. Two tests were conducted, surface roughness test and chemical surface analysis test. Results: Application of plasma treatment increased surface roughness for both oxygen and argon plasma treated acrylic resin specimen groups compared with control untreated group, with a highly significant difference (P <0.01) among groups. FTIR chemical analysis for oxygen plasma treated acrylic resin specimen group showed a spectrum with a broad peak, which represents the hydroxyl group (-OH). This was an important chemical change that increased the hydrophilicity as compared with FTIR spectrums of control and argon plasma treated acrylic resin groups which exhibited relatively the same peaks with mild chemical changes. Conclusion: Application of oxygen and argon plasma treatment represents an effective surface treatment method for increasing the surface roughness of acrylic resin denture base polymer material. Oxygen plasma treatment can activate the treated surface towards further chemical reactions, and increase the hydrophilicity of the acrylic resin denture base polymer material. Key words: Acrylic resin polymer, plasma treatment, surface roughness, FTIR analysis.